(untitled) (Research, Society and Development, 2022)
The aim of the present study was to evaluate the cytotoxic potential of a new complex of silver(I) with furosemide (Ag-FSE) over a panel of tumor and non-tumor human cells, as well as its genotoxicological safety. According to the results obtained, cell line derived from colorectal adenocarcinoma (Caco-2) was the most sensitive to the Ag-FSE complex, and among the non-tumor cells was the non-transforming fibroblasts known as GM07492A, which stimulated the characterization of cytotoxic properties against these cells. In addition to interfering with the cellular metabolic profile (evidenced by the resazurin method), Ag-FSE alters the integrity of cell membranes (results obtained by the Trypan blue assay) regardless of the cell line evaluated. However, interference with clonogenic capacity is dependent on the cell being tested; the cytotoxic activity evaluated by the clonogenic survival assay was evidenced against Caco-2 cells, but not against GM07492A cells. Furthermore, Ag-FSE did not induce an increase in the extent of DNA damage detectable by the comet assay, nor in the frequency of micronuclei compared to the negative control, demonstrating the absence of genotoxicity under the experimental conditions used. The data of the present study provide information on various biological aspects of the Ag-FSE complex and help in the generation of new drug candidates with potential to impact the health area, targeting cancer treatment.